Effects of Microtubule Stabilization by Epothilone B Depend on the Type and Age of Neurons - Eun-Hae Jang; Aeri Sim; Sun-Kyoung Im; Eun-Mi Hur (Neural Plasticity)
Several studies have demonstrated the therapeutic potential of applying microtubule- (MT-) stabilizing agents (MSAs) that cross the blood-brain barrier to promote axon regeneration and prevent axonal dystrophy in rodent models of spinal cord injury and neurodegenerative diseases. Paradoxically, administration of MSAs, which have been widely prescribed to treat malignancies, is well known to cause debilitating peripheral neuropathy and axon degeneration. Despite the growing interest of applying MSAs to treat the injured or degenerating central nervous system (CNS), consequences of MSA exposure to neurons in the central and peripheral nervous system (PNS) have not been thoroughly investigated. Here, we have examined and compared the effects of a brain-penetrant MSA, epothilone B, on cortical and sensory neurons in culture and show that epothilone B exhibits both beneficial and detrimental effects, depending on not only the concentration of drug but also the type and age of a neuron, as seen in clinical settings. Therefore, to exploit MSAs to their full benefit and minimize unwanted side effects, it is important to understand the properties of neuronal MTs and strategies should be devised to deliver minimal effective concentration directly to the site where needed.